Prognostic value of liver stiffness measurement for complications after allogeneic transplant with post-transplant cyclophosphamide - Bailén, Rebeca; Fernández-Villalobos, Manuel; Alonso, Sonia; Gómez-Centurión, Ignacio; Fernández-Caldas, Paula; Castilla, Lucía; Llácer, María José; Ahumada, Adriana; Iniesta, Carlos; Rincón, Diego; Muñoz, Cristina; Sabell, Santiago; et al. (Frontiers in Immunology, 2026)
IntroductionPre-existing comorbidities prior to allogeneic hematopoietic stem cell transplantation (HSCT), significantly affects outcomes. Prior hepatic impairment is included in classic prognostic scores like HCT-CI, without taking into consideration modern assessment techniques such as liver stiffness (LS) measurement. We aimed to evaluate the value of LS using Fibroscan (FS) to predict transplant outcomes and hepatic complications in patients undergoing allo-HSCT using post-transplant cyclophosphamide (PTCY) for graft-versus-host disease (GVHD) prophylaxis.MethodsWe conducted a single-center, prospective, observational study to evaluate the utility of LS measurement performed prior to transplantation and on day +14 to predict transplant outcomes, between October 2021 and March 2024. ROC curves were used to identify cut-off points for LS values for the development of hepatotoxicity, veno-occlusive disease (VOD), and hepatic acute and chronic GVHD. Logistic regression was used to analyse the impact of LS on overall survival (OS), event-free survival (EFS), non-relapse mortality (NRM) and graft-versus-host-disease and relapse-free survival (GRFS) .ResultsOne hundred eight patients were included. Median follow-up was 12.5 months. OS, EFS, GRFS, cumulative incidence of relapse and NRM at 12-months were 75%, 68%, 55%, 22% and 9%, respectively. Cumulative incidences of grade II-IV acute GVHD at day 180 and moderate-severe chronic GVHD at 12 months were 14% and 12%, respectively. Five patients (4.6%) developed VOD. LS variation (FSΔ) from baseline LS to day +14 was significantly increased in those patients who developed VOD compared to those who did not (p=0.048; AUROC 0.8). Logistic regression univariate analysis showed FS+14>6KPa to be predictive for worse OS and EFS (p<0.05). Multivariate analysis found FS+14>6 KPa to be predictive for worse EFS.DiscussionIn our experience, increase in LS between baseline and day +14 was predictive for VOD. In addition, a measurement of FS+14>6Kpa was predictive for the outcome of allo-HSCT, with an independently predictive value for worse EFS. Thus, FS+14>6 KPa should be considered in future prognostic models used for PTCY-based HSCT.